From structural biology to designing therapy for inborn errors of metabolism. Issue 4 (30th May 2016) - Yue, Wyatt W.
Abstract: At the SSIEM Symposium in Istanbul 2010, I presented an overview of protein structural approaches in the study of inborn errors of metabolism (Yue and Oppermann2011 ). Five years on, the field is going strong with new protein structures, uncovered catalytic functions and novel chemical matters for metabolic enzymes, setting the stage for the next generation of drug discovery. This article aims to update on recent advances and lessons learnt on inborn errors of metabolism via the protein‐centric approach, citing examples of work from my group, collaborators and co‐workers that cover diverse pathways of transsulfuration, cobalamin and glycogen metabolism. Taking into consideration that many inborn errors of metabolism result in the loss of enzyme function, this presentation aims to outline three key principles that guide the design of small molecule therapy in this technically challenging field: (1) integrating structural, biochemical and cell‐based data to evaluate the wide spectrum of mutation‐driven enzyme defects in stability, catalysis and protein‐protein interaction; (2) studying multi‐domain proteins and multi‐protein complexes as examples from nature, to learn how enzymes are activated by small molecules; (3) surveying different regions of the enzyme, away from its active site, that can be targeted for the design of allosteric activators and inhibitors.